Personalized pollen‐related symptom‐forecast information services for allergic rhinitis patients in Europe. Issue 8 (30th July 2013) - Berger, U.; Karatzas, K.; Jaeger, S.; Voukantsis, D.; Sofiev, M.; Brandt, O.; Zuberbier, T.; Bergmann, K. C.
Abstract: We report on the development of personalized pollen‐related information services that include sensitivity categorization, threshold identification, and symptom forecasting, addressing patients with allergic rhinitis in Europe.